Behavior of prestressed concrete-filled steel tube (CFST) beam. (1st September 2016) - Zhan, Yulin; Zhao, Renda; Ma, Zhongguo John; Xu, Tengfei; Song, Ruinian
Highlights: Eight prestressed CFST beams with large-scale section were tested under bending. Prestressing delays crack occurrence and enhances the composite action under bending. The flexural stiffness of prestressed CFST is better relative to non-prestressed CFST. Abstract: Concrete-filled steel tube (CFST) member is widely used for building, bridge and foundation structures because of its excellent performance. When a CFST member is subjected to axial loads, the filling concrete is confined by the steel tube, resulting in a tri-axial state of compression that improves its strength, stiffness and ductility. However, the cracking of concrete in tension zone would decrease this enhancement when the CFST member is subjected to flexure, especially when it is used as a major flexural member with large-scale section in bridges. To overcome this weakness, the prestressed CFST concept is investigated in this paper. Eight prestressed CFST beams with large-scale section (300 × 450 mm) were tested under bending. Two concrete strengths (C50 and C60) and two different degrees of prestressing (0.26 and 0.40) were studied in the experimental program. The full vibration and grouting method was introduced to gain a good performance of specimens. The perfobond rib shear connector was adopted to achieve the composite action. The flexural behaviors were verified by comparing with predictions from a proposed model considering the confinement effects. A simplified method is proposed to determine the ultimate moment capacity based on the plastic stress block hypothesis. Both experimental and analytical results show that the prestressed strands could significantly enhance the confinement effect of the core concrete under bending, which, in turn, improves the prestressed CFST beam performance in strength, stiffness and ductility.